Fewer hospitalizations and prolonged technique survival with home hemodialysis– a matched cohort study from the Swedish Renal Registry - Helena Rydell; Kerstin Ivarsson; Martin Almquist; Naomi Clyne; Mårten Segelmark (BMC Nephrology, 2019)
Abstract Background Patients on home hemodialysis (HHD) exhibit superior survival compared with patients on institutional hemodialysis (IHD) and peritoneal dialysis (PD). There is a sparsity of reports comparing morbidity between HHD and IHD or PD and none in a European population. The aim of this study is to compare morbidity between modalities in a Swedish population. Methods The Swedish Renal Registry was used to retrieve patients starting on HHD, IHD or PD. Patients were matched according to sex, age, comorbidity and start date. The Swedish Inpatient Registry was used to determine comorbidity before starting renal replacement therapy (RRT) and hospital admissions during RRT. Dialysis technique survival was compared between HHD and PD. Results RRT was initiated with HHD for 152 patients; these were matched with 608 patients with IHD and 456 with PD. Patients with HHD had significantly lower annual admission rate and number of days in hospital. (median 1.7 admissions; 12 days) compared with IHD (2.2; 14) and PD (2.8; 20). The annual admission rate was significantly lower for patients with HHD compared with IHD for cardiovascular diagnoses and compared with PD for infectious disease diagnoses. Dialysis technique survival was significantly longer with HHD compared with PD. Conclusions Patients choosing HHD as initial RRT spend less time in hospital compared with patients on IHD and PD and they were more likely than PD patients, to remain on their initial modality. These advantages, in combination with better survival and higher likelihood of renal transplantation, are important incentives for promoting the use of HHD.